What Investors Want : Perceptions and Experiences of Multinational Corporations in Developing Countries - Kusek, Peter; Silva, Andrea (World Bank, Washington, DC, 2018)
This paper discusses the results of a survey of multinational corporations with affiliates in developing countries. The paper explores corporate perspectives and decision making across the stages of the investment cycle: attraction, entry and establishment, operations and expansion, linkages with the local economy, and, in some cases, divestment and exit. Through interviews with 754 executives, the survey finds that political stability and a business-friendly regulatory environment are the top two factors influencing multinational corporations' investment decisions in developing countries. Investors seek predictable, transparent, and efficient conduct of public agencies. The survey results also show that investors are heterogeneous, and their perceptions vary with motivation and size. Multinational corporations that are involved in efficiency-seeking investment are more selective than investors motivated by other considerations, and that relatively smaller multinational corporations are more sensitive to host country characteristics and investment climate factors than large firms.